PROMOSI OBJEK WISATA PANTAI COROCOK PAINAN PESISIR SELATAN (PESSEL) DAN SEKITARNYA DALAM BENTUK AUDIO VISUAL - Hedo Putra; Ady Rosa; Idran Wakidi (DEKAVE : Jurnal Desain Komunikasi Visual, 2012)
AbstractCompletion of course visual communication design, fine art by the author, after considering the capabilities and weaknesses, the authors are more interested in choosing courses work late, because trends I like to practice courses that could provoke creativity, compared with a theoretical activities and kesehariaan author of more dominated by the activities of the practice. Themes raised in this final work is the promotion of coastal attractions corocok Painan south coast and surrounding areas in the form of audio visual, originated from the interest the authors listened Painan city's attractions can be seen from theelectronic media, print media and other media that makes the author so anxious to raise campaign lunge attraction corocok Painan south coast beaches and surrounding areas in the work of a writer working on the end in the form of audio visual. Later in this final work containing about promotional profile corocok Painan attractions and surrounding beaches, ranging from the history, vision, mission, and goals, as well as the benefits wisara. supporting medium, such as key chains, pins, digital print T-shirts, calendars, mugs, clocks, pens, stickers, and x banner.Kata kunci : Wisata, Audio, Visual.